Kinetic evidence of magnetic reconnection due to Kelvin‐Helmholtz waves. Issue 11 (11th June 2016) - Li, W.; André, M.; Khotyaintsev, Yu. V.; Vaivads, A.; Graham, D. B.; Toledo‐Redondo, S.; Norgren, C.; Henri, P.; Wang, C.; Tang, B. B.; Lavraud, B.; Vernisse, Y.; et al.
Abstract: The Kelvin‐Helmholtz (KH) instability at the Earth's magnetopause is predominantly excited during northward interplanetary magnetic field (IMF). Magnetic reconnection due to KH waves has been suggested as one of the mechanisms to transfer solar wind plasma into the magnetosphere. We investigate KH waves observed at the magnetopause by the Magnetospheric Multiscale (MMS) mission; in particular, we study the trailing edges of KH waves with Alfvénic ion jets. We observe gradual mixing of magnetospheric and magnetosheath ions at the boundary layer. The magnetospheric electrons with energy up to 80 keV are observed on the magnetosheath side of the jets, which indicates that they escape into the magnetosheath through reconnected magnetic field lines. At the same time, the low‐energy (below 100 eV) magnetosheath electrons enter the magnetosphere and are heated in the field‐aligned direction at the high‐density edge of the jets. Our observations provide unambiguous kinetic evidence for ongoing reconnection due to KH waves. Key Points: Magnetosheath electrons enter magnetosphere and magnetospheric electrons escape due to reconnection Field‐aligned heating of magnetosheath electrons at the high‐density edges of the jets Gradual ion mixing across the magnetopause